Principal's Transformational Leadership for Strengthening Religious Values at SD Negeri Banyuraden Yogyakarta - Septariani, Sella Fadia (Universitas Muhammadiyah Yogyakarta, 2024)
Transformational leadership has attracted various attention as one of the appropriate leadership styles applied by school principals to improve religious values ​​as proven from previous studies on the transformational leadership paradigm of school principals at the Senior High School (SMA) level. Therefore, further research on the application of these principles at the primary education level is essential. The current research aims to investigate the application of transformational leadership at the elementary school (SD) level to strengthen religious values. The research was carried out at SDN Banyuraden, Gamping, Sleman, Yogyakarta for two months, from October to December 2023, using a descriptive qualitative approach with two subjects consisting of the principal and Islamic Religious Education (PAI) teacher. The instruments used were interview transcripts and documentation instruments which were prepared based on leadership, transformational and religious value variables. Data analysis was carried out in three stages: 1) data reduction, 2) data presentation and 3) drawing conclusions. Based on the results found in this research, leadership practices at SDN Banyuraden show a strong commitment to implementing transformational leadership principles to build a school environment based on religious values. The Principal of SDN Banyuraden provides an example and conveys religious messages to students and school staff. The consistency and commitment shown by the principal is an important step towards the vision of a more religious school with a commitment to religious values. However, challenges in growing student morale and efforts to expand innovation in education remain the focus of improvement. In conclusion, this article highlights the importance of implementing transformational leadership in strengthening religious aspects in the educational environment. However, achieving optimal results will require significant effort and unwavering support from all individuals involved in the institution.